Effect of adding herbs Sage, Marjoram and industrial anti-oxidants BHT to diets and its impact on productivity characteristics in broiler - Majid, Ahmed Abdul-Rahmman; Abdul-Jabbar, Abdul-Jabbar Abdul-Kareem; Aloan, Muthana Abdul-Hammed (Journal of Kerbala for Agricultural Sciences, 2016)
Experiment conducted at poultry field of College of Agriculture/ University of Anbar. The experiment used 240 broiler chicks from (Ross 308) breed of day-old for the period 05/ 24/ 2013 to 04/ 07/ 2013, Distributed randomly to eight transactions were herb Sage and Marjoram added at (1%) level and BHT (Butylated Hydroxyl Toluene) compound at (0.01%) level. Compared with control group for 42 days. The experiment goal was to ensure the positive and negative effects of the treatments which used additives. The results of the experiment showed significant improvement (P≤0.05) on feed consumption by adding 1% of Marjoram in the diet and obtain significant superiority (P≤0.05) in living body weight, weight increase and efficiency of feed conversion by adding 1% of Sage and Marjoram mixture in the diet.